PARTISIPASI MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH - ', Komperensi; ', Yoserizal (Universitas Riau, 2013)
The purpose of this study is to investigateand analyze the factors that influence people’s participation in local elections Regency KuantanSingingi Year 2011. This research was conducted in the district Singingi Kuantan, where theinformant research is community leaders, religious leaders, youth leaders, prominent intellectuals,the Election Commission and the public. Data collected by interview and observation techniques,after the data was collected and then analyzed using qualitative descriptive analysis. The resultshowed that people’s participation in local elections in Kuantan District Singingi Year 2011 can besummed up quite well. While the factors most likely to influence people’s participation in localelections in Kuantan District Singingi factor is the willingness and the capacity factor.